Pembelajaran Berbasis E-Learning di Madrasah; Tantangan dan Peluang - Ahmad Jaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this paper is to elaborate on E-Learning-based learning in madrasas. The research method used is library research method with a qualitative approach. The research results show that the basic concepts of e-learning-based learning in madrasas actually include: a) having content that is relevant to the learning objectives; b) using instructional methods c) using media elements, d) enabling direct teacher-centered learning (synchronous e-learning) e) building understanding and skills related to learning objectives. The challenges and opportunities of e-learning-based learning can be a very supportive and preferred learning medium for students. The content is also a stimulus for students to be reactive and innovate through technology. However, the challenge faced is the uneven distribution of educational institutions with sufficient learning facilities. This is what must be understood together, so that it becomes a big concern, especially for policy makers.